2018
DOI: 10.1242/jeb.180869
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic and acute stressors, and their interaction, on testes function: an experimental test during testicular recrudescence

Abstract: Organisms are expected to invest less in reproduction in response to a stressor, but theory predicts that this effect should depend on the frequency and duration of stressors in the environment. Here, we investigated how an acute stressor affected testes function in a songbird, and how chronic stressors influenced the acute stress response. We exposed male dark-eyed juncos () either to chronic or minimal (control) disturbance during testicular recrudescence, after which we measured baseline testosterone, testo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 88 publications
2
2
0
Order By: Relevance
“…Furcular fat stores did not appear to be sensitive to fire in either the comparison to previous study years or in the paired pre fire versus post fire analysis, suggesting that males did not suffer from diminished body condition in response to fire. Finally, we did not find a relationship between corticosterone and testosterone in our dataset (Supporting information), thus adding to a growing list of studies in birds suggesting an absence of antagonism between these two hormones (Davies et al 2016, Deviche et al 2017, Abolins‐Abols et al 2018).…”
Section: Discussionsupporting
confidence: 54%
“…Furcular fat stores did not appear to be sensitive to fire in either the comparison to previous study years or in the paired pre fire versus post fire analysis, suggesting that males did not suffer from diminished body condition in response to fire. Finally, we did not find a relationship between corticosterone and testosterone in our dataset (Supporting information), thus adding to a growing list of studies in birds suggesting an absence of antagonism between these two hormones (Davies et al 2016, Deviche et al 2017, Abolins‐Abols et al 2018).…”
Section: Discussionsupporting
confidence: 54%
“…In addition, this limited sampling window could have kept us from detecting diminished fat stores following fire (Table 1). Finally, we did not find a relationship between corticosterone and testosterone in our dataset ( Figure S1), thus adding to a growing list of studies in birds suggesting an absence of antagonism between these two hormones (Davies et al 2016, Deviche et al 2017, Abolins-Abols et al 2018.…”
Section: Unornamented Ornamentedsupporting
confidence: 46%
“…Alternatively, the exercise of flying and hopping during disturbances may have interfered with mass gain in the disturbance group. A companion study of these same birds found that frequently-disturbed birds were equally reproductively ready as control birds: groups did not differ in testes mass or testosterone in response to GnRH, and cloacal protuberance size was larger in the disturbance group, although baseline testosterone was lower in the disturbance group (Abolins-Abols et al, 2018). These results indicate that birds in the chronic disturbance treatment were likely not in homeostatic overload (Romero et al, 2009), and were instead able to achieve reproductive readiness despite disturbances, suggesting that the phenotypic flexibility we observed was adaptive (Ghalambor et al, 2007).…”
Section: Body Conditionmentioning
confidence: 92%